Mathematical Communication Skills of Students with Adversity Quotient Personality in Solving Story Problems Reviewed from Information Processing Theory - Asmira Sudiman; Rusdyi Habsyi; Lisnawati Soamole (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study investigates the cognitive mechanisms underlying students' mathematical communication in solving story problems by integrating Adversity Quotient (AQ) and Information Processing Theory. Although mathematical communication has been widely recognized as a key component of mathematical proficiency, limited research has explained how students' resilience-related dispositions shape the cognitive processes through which mathematical ideas are understood, organized, and communicated. A qualitative case study was conducted with 32 eighth-grade students at SMP Negeri 2 Halmahera Barat, Indonesia. Data were collected through validated open-ended story-problem tasks, AQ classification, students' written work, and semi-structured interviews. The analysis combined descriptive categorization of mathematical communication with thematic analysis based on four cognitive processing stages: attention, perception, retrieval, and encoding. The findings show that students' mathematical communication was generally low, with 17 students in the very low category. Cross-case analysis revealed distinct patterns across AQ profiles. Climbers demonstrated relatively complete cognitive processing cycles and coherent mathematical explanations. Campers showed partial processing, especially in strategy formulation, retrieval accuracy, and justification. Quitters experienced breakdowns from the attention stage, resulting in fragmented or absent mathematical communication. This study proposes a conceptual model in which AQ functions as a resilience-related regulator of cognitive processing continuity, thereby shaping mathematical communication outcomes. The findings contribute to mathematics education by offering a process-based explanation of communication difficulties and by emphasizing the need for instruction that supports both cognitive processing and resilience in problem solving.